WATER SOLUBLE COVALENT CONJUGATES OF Aspergillus oryzae ALPHA AMYLASE WITH DEXTRAN SULPHATE AND THEIR FLUORESCENCE CHARACTERISTICS - Altikatoglu, Melda; Kuzu, Huriye (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2009)
The polyaldehyde derivative of water-soluble dextran sulphate (DS) (M-w: 500 000 Da) was covalently coupled to Aspergillus oryzae alpha-amylase (EC 3.2.1.1) in aqueous solution with different molar ratios (n(enzyme)/n(polymer): 10, 20, 30). These conjugates were obtained by multi-point covalent bonding of dextran sulphate aldehyde to the enzyme. The aldehyde group is responsible for covalent bonding, and the negatively charged sulphate group provides electrostatic attraction of the positively charged biomolecules. The conformational changes of the enzyme molecule in conjugates were observed using fluorescence techniques. These studies revealed that the enzyme molecules in conjugates were stretched and more exposed to water molecules in aqueous solutions. The conjugation caused the expansion of pH activity range of the enzyme through the lower pH.
Keywords: Aspergillus oryzae alpha-amylase; dextran sulphate; covalent conjugates; activity; fluorescence; AMPHIPHILIC IMMUNOGENS; TRYPTOPHAN; PROTEIN; STABILITY; AFFINITY; ALBUMIN; Environmental Sciences & Ecology